Effectiveness Of Administration Melon Juice On Lowering Blood Pressure In KB Acceptors Injecting Depo Medroxy Progesterone Aceteat The Bambang Health Center, West Sulawesi Province 2022 - Musdalifah Musdalifah (Lembaga Pengembangan Kinerja Dosen, 2023)
One of the problems caused by use of depo-medroxy progesterone acetate injection KB is increased blood pressure so many KB acceptors stop using contraception especially hormonal KB. Then, to overcome the increase in blood pressure in KB acceptors, it can be recommended to consume melon juice. The purpose this study was to determine the effectiveness of administering melon juice in reducing blood pressure in acceptors of depot-medroxy progesterone acetate injections at the Bambang Community Health Center, West Sulawesi Province. The type of research used was pre-experimental with a one group pretest-posttest design. The research sample consisted of 30 mothers who received depo-medroxy progesterone acetate injections for KB and who had increased blood pressure who visited the Bambang Community Health Center who were given melon juice. The results showed that was an effect of giving melon juice on reducing blood pressure in KB acceptors of the depo-medroxy progeteron acetate injection with a value of ρ=0.000. It hoped that it can become a source of information for all health agencies as a material consideration so that the asministrasion of melon juice to be developed.